Viral Voices in Language Learning: The Role of TikTok English Songs in Enhancing EFL Learners’ Vocabulary Retention - Nabila Rana Hanansi; Nuri Fitriyah; Konitatul Maghfirah; Nasrullah Nasrullah; Musbehah Musbehah; Henny Uswatun Hasanah (Journal of English Education, 2025)
TikTok has evolved as one of the most influential internet platforms in recent years. TikTok, recognized for its brief videos and viral phenomena, provides a diverse array of audio-visual content, including music-centric material that frequently incorporates popular English songs. This study investigates the use of popular English TikTok songs as authentic digital materials to enhance vocabulary retention in an EFL (English as a Foreign Language) context. With the growing integration of digital media in students’ daily lives, platforms like TikTok offer engaging and context-rich opportunities for language learning. Adopting qualitive method through case study design, this research explored the experiences, perceptions, and learning behaviors of students at SMAN 1 Pamekasan who actively used TikTok and engaged with English songs on the platform. Data were collected through semi-structured interview with 3 participants, Thematic analysis revealed three main findings: (1) the songs significantly increased learners’ motivation and engagement; (2) vocabulary retention improved due to repeated and contextualized exposure to language; and (3) emotional and social interactions supported deeper learning. The results suggest that integrating familiar and enjoyable content such as TikTok songs into classroom instruction can bridge the gap between formal education and students’ digital experiences, leading to more meaningful and effective vocabulary acquisition. These findings highlight the pedagogical value of leveraging students' media habits to support learner-centered and engaging language instruction.